Bacillus spp. isolated from pepper leaves and their function and inhibition of the fungal plant pathogen Colletotrichum scovillei - Lijuan Wei; Chengde Yang; Lingxiao Cui; Mengjun Jin; Richard Osei (Egyptian Journal of Biological Pest Control, 2023)
Abstract Background Pepper is a popular ingredient in many Chinese households; however, anthracnose caused by Colletotrichum spp. has greatly decreased pepper production. The genus Bacillus is widely known for its important role in the development and protection of plants from phytopathogenic fungi. Results Fifty-eight endophytic strains were isolated from pepper leaves and tested for antifungal activity in this study. Specifically, L1-7 and L3-5 displayed growth inhibition rates of 79 and 80% against C. scovillei mycelium, respectively, while 25 of these strains all had growth inhibition rates of greater than 60%. Bacillus amyloliquefaciens and B. velezensis, based on culture and morphological identification with 16S rDNA and gyrB gene sequence analyses, were determined to be the respective species L1-7 and L3-5. Additionally, it was discovered that these two antagonistic endophytic bacteria could fix nitrogen, produce indoleacetic acid (IAA) and have a high salt tolerance. Pot experiments again showed excellent control of the pathogen C. scovillei by L1-7 and L3-5, with 80.64 and 73.39% control, respectively. Therefore, B. amyloliquefaciens (L1-7) and B. velezensis (L3-5) can be applied as biological control agents to protect peppers against C. scovillei-caused anthracnose. Conclusion Bacillus amyloliquefaciens (L1-7) and B. velezensis (L3-5) can be applied as biological control agents to protect peppers against C. scovillei-caused anthracnose. Thus, they can serve as promising biocontrol agents and plant growth promoters, and future research on the pertinent bacteria will serve as a useful guide for the creation of microbial resources.